Fault location in power distribution systems considering a dynamic load model - Harold Andres Cifuentes Chaves; Daniel Fernando Patiño Ipus; Juan Jose Mora Flórez (Ingeniería e Investigación, 2015)
In the electrical power systems, load is one of the most difficult elements to be represented by an adequate mathematical model due to its complex composition and dynamic and non-deterministic behavior. Nowadays, static and dynamic load models have been developed for several studies such as voltage and transient stability, among others. However, on the issue of power quality, dynamic load models have not been taken into account in fault location. This paper presents a fault location technique based on sequence components, which considers static load models of constant impedance, constant current and constant power. Additionally, an exponential recovery dynamic load model, which is included in both the fault locator and the test system, is considered. This last model is included in order to consider the dynamic nature of the load and the performance of the fault locators under this situation. To demonstrate the adequate performance of the fault locator, tests on the IEEE 34 nodes test feeder are presented. According to the results, when the dynamic load model is considered in both the locator and the power system, performance is in an acceptable range.